H (2)-stabilization of the Isothermal Euler equations: a Lyapunov function approach - Gugat, Martin; Leugering, Günter; Tamasoiu, Simona Oana; Wang, Ke (Chinese Annals of Mathematics Series B, 2012)
The authors consider the problem of boundary feedback stabilization of the 1D Euler gas dynamics locally around stationary states and prove the exponential stability with respect to the H (2)-norm. To this end, an explicit Lyapunov function as a weighted and squared H (2)-norm of a small perturbation of the stationary solution is constructed. The authors show that by a suitable choice of the boundary feedback conditions, the H (2)-exponential stability of the stationary solution follows. Due to this fact, the system is stabilized over an infinite time interval. Furthermore, exponential estimates for the C (1)-norm are derived.
Keywords: Boundary control; Feedback stabilization; Quasilinear hyperbolic system; Balance law; Gas dynamics; Isothermal Euler equations; Exponential stability; Lyapunov function; H-2-norm; Stationary state; Characteristic variable; 76N25; 35L50; 93C20